Tourism Consumption and Representation Narratives of Place and Self - Meethan, Kevin (CABI, 2014)
This volume addresses some new developments in approaches towards tourism analysis that focus on the interface between the production and consumption of tourist space, the narratives that are created around specific sites and specific forms of tourist activity, and the ways in which these are created, picked up, modified and incorporated into the narratives of self-hood that we all weave around our lives and the identities of the places in which we live. Tourism research itself is continuing to develop away from early business and geographical models towards approaches more informed by other social sciences, in particular anthropology and sociology. In many ways, what we are seeing in tourism studies, if one can coin that term, is a replication of what is happening 'out there'.